2019
DOI: 10.1126/scitranslmed.aao0498
|View full text |Cite
|
Sign up to set email alerts
|

Sustained correction of associative learning deficits after brief, early treatment in a rat model of Fragile X Syndrome

Abstract: Fragile X Syndrome (FXS) is one of the most common monogenic forms of autism and intellectual disability. Preclinical studies in animal models have highlighted the potential of pharmaceutical intervention strategies for alleviating the symptoms of FXS. However, whether treatment strategies can be tailored to developmental time windows that define the emergence of particular phenotypes is unknown. Similarly, whether a brief, early intervention can have long-lasting beneficial effects, even after treatment cessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 54 publications
5
69
0
Order By: Relevance
“…In 2002, it was found that mGluR-LTD at hippocampal CA3:CA1 synapses is exaggerated in Fmr1 KO mice 75 and it was later discovered that in the absence of FMRP, mGluR-LTD no longer requires new protein synthesis 129 . The mGluR-LTD pathway has been targeted in multiple pharmacological studies aimed at developing treatments for FXS 19,[130][131][132][133][134][135][136] , yet we still have a limited understanding of which mRNAs regulated by FMRP are the most important for altered mGluR-LTD phenotypes 19 . mGluR-LTD is central to motor learning tasks mediated by Purkinje cells, evidenced by impairment of conditioned eyeblink responses in global mGluR1 KO mice that can be rescued by Purkinje cell-specific mGluR1 expression 137,138 .…”
Section: Loss Of Function Of Fmrp Causes Altered Behavior and Cognitimentioning
confidence: 99%
“…In 2002, it was found that mGluR-LTD at hippocampal CA3:CA1 synapses is exaggerated in Fmr1 KO mice 75 and it was later discovered that in the absence of FMRP, mGluR-LTD no longer requires new protein synthesis 129 . The mGluR-LTD pathway has been targeted in multiple pharmacological studies aimed at developing treatments for FXS 19,[130][131][132][133][134][135][136] , yet we still have a limited understanding of which mRNAs regulated by FMRP are the most important for altered mGluR-LTD phenotypes 19 . mGluR-LTD is central to motor learning tasks mediated by Purkinje cells, evidenced by impairment of conditioned eyeblink responses in global mGluR1 KO mice that can be rescued by Purkinje cell-specific mGluR1 expression 137,138 .…”
Section: Loss Of Function Of Fmrp Causes Altered Behavior and Cognitimentioning
confidence: 99%
“…By this mechanism, lovastatin has been shown to successfully correct electrophysiological and behavioural phenotypes in the mouse model of Neurofibromatosis Type 1 (NF1), a neurodevelopmental disorder of excess Ras [20].In the Fmr1 -/y mouse, the reduction of Ras-ERK1/2 by lovastatin ameliorates hippocampal epileptogenesis and neocortical hyperexcitability and significantly reduces the incidence of AGS [15]. Additionally, studies using the Fmr1 -/y rat model show that lovastatin treatment at a juvenile age can prevent the emergence of complex cognitive phenotypes [21]. Based on the positive outcome with lovastatin in Fmr1 -/y animal models, two open-label clinical trials tested the viability of lovastatin for the treatment of FX [22,23].…”
mentioning
confidence: 99%
“…It is interesting to note that, although ADCY1, ERK1/2, and Akt are pro-learning molecules and their activity is required for memory formation 26,[35][36][37] , the elevated activity of these signaling molecules is concurrent with the learning deficits in FXS. It is evident that decrease rather than increase of the activity of ADCY1, ERK1/2 and Akt shows therapeutic efficacy to correct cognitive impairments in FXS mouse 38,39 . Although the mechanism remains elusive, it is possible that concurrent increase of ADCY1, ERK1/2 and Akt activity along with other pathological changes in FXS impair rather than facilitate learning.…”
Section: Discussionmentioning
confidence: 99%